The Effect of Duty Hour Regulation on Resident Surgical Case Volume in Otolaryngology. (October 2014) - Curtis, Stuart H.; Miller, Robert H.; Weng, Cindy; Gurgel, Richard K.
Objective: Evaluate the effect of duty hour regulation on graduating otolaryngology resident surgical case volume and analyze trends in surgical case volume for Accreditation Council for Graduate Medical Education (ACGME) key indicator cases from 1996 to 2011. Study Design: Time-trend analysis of surgical case volume. Setting: Nationwide sample of otolaryngology residency programs. Subjects: Operative logs from the American Board of Otolaryngology and ACGME for otolaryngology residents graduating in the years 1996 to 2011. Methods: Key indicator volumes and grouped domain volumes before and after resident duty hour regulations (2003) were calculated and compared. Independent t test was performed to evaluate overall difference in operative volume. Wilcoxon rank sum test evaluated differences between procedures per time period. Linear regression evaluated trend. Results: The average total number of key indicator cases per graduating resident was 440.8 in 1996-2003 compared to 500.4 cases in 2004-2011, and overall average per number of key indicators was 31.5 and 36.2, respectively ( P = .067). Four key indicator cases showed statistically significant ( P < .05) increases in volume after duty hour implementation. General/pediatrics was the only grouped domain to show a significant increase. In contrast, the rate of change in operative volume decreased post duty hour for only 2 key indicators ( P < .05). The year-by-year trend in average operative volume showed significant increases for 5 key indicator cases ( P < .05). Conclusion: Implementation of the 2003 duty hour regulations has not reduced total volume of key indicator cases for graduating otolaryngology residents. The overall trend in operative volume is increasing for several specific key indicators.